Life problems in children and adolescents who self‐harm: findings from the multicentre study of self‐harm in England. Issue 4 (18th January 2022) - Townsend, Ellen; Ness, Jennifer; Waters, Keith; Rehman, Muzamal; Kapur, Navneet; Clements, Caroline; Geulayov, Galit; Bale, Elizabeth; Casey, Deborah; Hawton, Keith
Abstract : Background: Self‐harm, a significant and increasing global problem in children and adolescents, is often repeated and is associated with risk of future suicide. To identify potential interventions, we need to understand the life problems faced by children and adolescents, and by sub‐groups of younger people who self‐harm. Our aims were to include the following: (a) investigate the type and frequency of life problems in a large sample of children and adolescents who self‐harmed. (b) Examine whether problems differ between those who repeat self‐harm and those who do not. Methods: We analysed data for 2000 to 2013 (follow up until 2014) from the Multicentre Study of Self‐harm in England on individuals aged 11 to 18 years who presented to one of the five study hospitals following self‐harm and received a psychosocial assessment including questions about problems, which precipitated self‐harm. Results: In 5648 patients (12, 261 self‐harm episodes), (75.5% female, mean age 16.1 years) the most frequently reported problems at first episode of self‐harm were family problems. Problems around study/employment/study and relationships with friends also featured prominently. The types of problems that precede self‐harm differed between late childhood/early adolescence. Abuse, mental health problems and legal problems significantly predicted repeat self‐harm for females. Conclusion: The most common problems reported by both genders were social/interpersonal in nature, indicating the need for relevant services embedded in the community (e.g. in schools/colleges). Self‐harm assessment and treatment choices for children and adolescents must take age and gender into account. To prevent future self‐harm, individualised supports and services are particularly needed for abuse, mental health and legal problems.